THE COMMUNICATION STRATEGY USED BY TEACHERS IN TEACHING ENGLISH AT SMPN 19 KOTA JAMBI IN ACADEMIC YEAR 2017/2018 - Nova Ria Ningsy; Wennyta Wennyta; Nurul Fitri (Universitas Batanghari Jambi, 2018)
The purpose the of the research is to find out what are the communication strategy used by teacher in teaching English at SMPN 19 Kota Jambi in academic year 2017/2018. The method applied in conducting this research is descriptive qualitative. The subject of this research is four English teachers at SMPN 19 Kota Jambi. In collecting the data, the researcher use classroom observation and interview. The result of this research there are two communication strategies used by teachers while teaching English, namely two-ways communication and transactional communication. Based on the observation and interview result the researcher have concluded that the teacher often using various communication strategy in teaching English, namely two-ways communication and transactional communication. Moreover English teacher often use two-ways communication in teaching English rather than using transactional communication. It will make it easy for the students to understand the subject.Keywords: Communication Strategy, Teaching English